Mengintegrasikan Peran Gender dalam Analisis Intelijen Strategis: Partisipasi Perempuan dalam Kelompok Teroris di Indonesia - Priscilla Harjanti; Margaretha Hanita; Eko Daryanto (Syntax Corporation, 2023)
Women's roles in terrorist groups can vary depending on the specific organization, ideology, and cultural context. While traditionally women have been viewed as passive participants or solely confined to support roles, there has been a growing recognition of their active and diverse involvement in extremist activities. This study highlights the importance of understanding the roles women play within terrorist groups and their impact on operational strategies. By considering gender dynamics, intelligence analysis becomes more accurate and comprehensive. Gender-sensitive analysis helps uncover hidden or underestimated threats. Terrorist organizations and extremist movements may exploit gender norms and expectations to recruit, radicalize, and mobilize individuals. Acknowledging how gender influences recruitment strategies and identifying the unique vulnerabilities of certain groups, can help identify potential threats that might otherwise go unnoticed. This also benefits intelligence analysis as it can better inform preventive measures, protect vulnerable populations, and address the diverse needs and experiences of individuals affected by terrorism. This study aims to contribute to a broader discussion on gender perspectives in counterterrorism efforts and strategic intelligence analysis. It emphasizes the need for gender-sensitive intelligence analysis to enhance prevention and mitigation strategies in the field of counterterrorism and intelligence, ultimately aiming to enhance counterterrorism policies and practices.